2018
DOI: 10.1111/tra.12570
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of early endosomes across eukaryotes: Evolution and functional homology of Vps9 proteins

Abstract: Endocytosis is a crucial process in eukaryotic cells. The GTPases Rab 5, 21 and 22 that mediate endocytosis are ancient eukaryotic features and all available evidence suggests retained conserved function. In animals and fungi, these GTPases are regulated in part by proteins possessing Vps9 domains. However, the diversity, evolution and functions of Vps9 proteins beyond animals or fungi are poorly explored. Here we report a comprehensive analysis of the Vps9 family of GTPase regulators, combining molecular evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 85 publications
(146 reference statements)
0
12
0
Order By: Relevance
“…VARP, VPS29 and TBC1D5 are all ancient proteins, present in the Last Eukaryotic Common Ancestor 5 , 55 , 56 . However, co-occurrence need not necessarily indicate interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VARP, VPS29 and TBC1D5 are all ancient proteins, present in the Last Eukaryotic Common Ancestor 5 , 55 , 56 . However, co-occurrence need not necessarily indicate interaction.…”
Section: Resultsmentioning
confidence: 99%
“…VARP homologues were identified using HMMer 73 . A hidden Markov model was generated using phylogenetically verified holozoan VARP homologues published in Herman et al 56 , which was used to search predicted proteins from the genomes listed in Supplementary Table 2. All hits were then used as queries in BLASTP searches into the Homo sapiens genome 74 .…”
mentioning
confidence: 99%
“…A study of the evolution of the Vps9 domain showed 3 independent instances of acquisition of structurally diverse UBDs: the ZnF in mammalian Rabex5, the CUE domain in yeast, and a UBD in the amebozoan Sexangularia sp. (Herman, Ali et al, 2018). The fact that Vps9 domain containing proteins had such a strong tendency to acquire UBD through independent means suggests a critical role for UBDs in regulating Vps9 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the endocytic process involves transitioning through additional compartments that are defined by Rab21 (Tb927.10.1520), Rab28 (Tb927.6.3040), and finally Rab7 (Tb927.9.11000) [ 29 , 30 , 31 ]. Quite what the specific functions of these steps are remains to be elucidated but control does appear to be mediated by the vacuolar protein sorting 9 (Vps9) domain proteins, such as Alsin (Tb927.3.2430) and Rabex5 + GAPVD1 (Tb927.10.10020), a mechanism that is conserved with mammalian cells [ 32 ].…”
Section: A Dynamic Surface For Host and Environmental Interactionsmentioning
confidence: 99%